Answer: c) 14,871
Step-by-step explanation:
See photo attached - if my work doesn’t make sense I can explain it, just ask (:
Answer:
Its -2
Step-by-step explanation:
Let's solve your equation step-by-step.
−12−4x+3=−1
Step 1: Simplify both sides of the equation.
−12−4x+3=−1
−12+−4x+3=−1
(−4x)+(−12+3)=−1(Combine Like Terms)
−4x+−9=−1
−4x−9=−1
Step 2: Add 9 to both sides.
−4x−9+9=−1+9
−4x=8
Step 3: Divide both sides by -4.
−4x
−4
=
8
−4
x=−2
Answer:
Just need points
Step-by-step explanation:
Sorry
3.14*d
3.14*12= 37.68
Rounded to the nearest hundredth would be 37.7
Answer:
1.5 seconds
Step-by-step explanation:
i took a test with the same question